The Effectiveness of Sleep Hygiene on Sleep Quality Cancer Patients Undergoing Chemotherapy: A literature Review - Setia, Vovi Meidas; Rosa, Elsye Maria (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Cancer occurs due to disruption of the function of Deoxyribonucleic Acid (DNA) which can increase cell growth significantly to cell proliferation in cells. The purpose of this study was to provide information on effective sleep hygiene therapy on the sleep quality of cancer patients undergoing chemotherapy. The research method using the PRISMA database using Google Scholar, PubMed, ScienceDirect, ProQuest and Scopus data focuses on the last five years, from 2018 to 2023. Data is selected by referring to the "Mendeley and Rayyan" application independently to filter from screening, the results are selected by activating blind rayyan mode so that they can be selected together. The literature is an option to be able to identify sleep hygiene therapy trials given to cancer patients who experience sleep quality problems.  JBI is a critical assessment tool used to determine the quality of journals. The results of the article we included showed significant results and can be given to cancer patients who have poor sleep quality and are also beneficial for fatigue. Conclusions based on the results of the review of sleep hygiene interventions have a positive value on sleep quality and severity of cancer patients undergoing chemotherapy. Keywords: cancer, sleep hygiene, sleep quality, chemotherapy